2016
DOI: 10.1073/pnas.1521098113
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-276 promotes egg-hatching synchrony by up-regulating brm in locusts

Abstract: Developmental synchrony, the basis of uniform swarming, migration, and sexual maturation, is an important strategy for social animals to adapt to variable environments. However, the molecular mechanisms underlying developmental synchrony are largely unexplored. The migratory locust exhibits polyphenism between gregarious and solitarious individuals, with the former displaying more synchronous sexual maturation and migration than the latter. Here, we found that the egg-hatching time of gregarious locusts was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 54 publications
1
78
0
1
Order By: Relevance
“…miRNAs were usually negatively correlated with their targeted mRNAs, in spite of a few exceptions (He et al, 2016). The datasets of differentially expressed miRNAs and transcripts were integrated to identify the potential miRNA‐regulated target genes based on the following criteria: (a) miRNAs and mRNAs should be simultaneously and reversely changed in our analyses; (b) mRNAs should be predicted by miRNAs from software of RNAhybrid, Targetscan, and miRanda.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs were usually negatively correlated with their targeted mRNAs, in spite of a few exceptions (He et al, 2016). The datasets of differentially expressed miRNAs and transcripts were integrated to identify the potential miRNA‐regulated target genes based on the following criteria: (a) miRNAs and mRNAs should be simultaneously and reversely changed in our analyses; (b) mRNAs should be predicted by miRNAs from software of RNAhybrid, Targetscan, and miRanda.…”
Section: Methodsmentioning
confidence: 99%
“…Epigenetic modulations encompass covalent chemical modifications of DNA (Razin & Riggs, 1980) and histone (Strahl & Allis, 2000) as well as the production of non-coding RNAs such as small interfering RNA (siRNA), microRNA (miRNA), Piwi-interacting RNA (piRNA), and transfer RNA (tRNA) fragments (Bartel, 2004;Flanagan & Wild, 2007;Mohammad et al, 2012;Chen et al, 2016;Sharma et al, 2016). Increasing evidence suggests that certain epigenetic changes, such as DNA methylation (Morgan et al, 1999;Rakyan et al, 2003;Carone et al, 2010;Franklin et al, 2010;Padmanabhan et al, 2013;Radford et al, 2014;Wei et al, 2014), histone modification (Katz et al, 2009;Greer et al, 2011;Seong et al, 2011;Ost et al, 2014;Siklenka et al, 2015), siRNA (Rechavi et al, 2011(Rechavi et al, , 2014Conine et al, 2013;HouriZe'evi et al, 2016), miRNAs (Gapp et al, 2014;Rodgers et al, 2015;He et al, 2016), piRNA (Ashe et al, 2012), and tRNA fragments Sharma et al, 2016) (Table 1) can be transmitted from parents to their offspring through the germline. Thus, the inheritance of epigenetic states may allow organisms to deliver either adaptive or non-adaptive/pathological information related to the ancestral environment to their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that miRNAs can target the 5 â€Č -UTR or coding regions (CDS) of mRNA, activating the transcription of target genes Yang et al 2014;He et al 2016). At present, 3119 miRNA precursors corresponding to 3824 mature miRNAs have been identified in 26 insects and deposited in miRBase (Ylla et al 2016).…”
Section: Introductionmentioning
confidence: 99%